Continental Arc and Back-Arc Migration in Eastern NE China: New Constraints on Cretaceous Paleo-Pacific Subduction and Rollback - Sun, M.; Chen, H.; Milan, L.; Wilde, Simon; Jourdan, Fred; Xu, Y. (American Geophysical Union, 2018)
Tectonic evolution models for the Cretaceous Russia Sikhote-Alin and eastern NE China continental margin and interior remain controversial. To understand the magmatic evolution over time and assess regional geodynamic processes, we sampled a diverse array of igneous rocks and employed zircon U-Pb dating, hornblende and plagioclase 40Ar-39Ar dating, whole-rock major and trace element analysis, and 87Sr/86Sr and 143Nd/144Nd isotopic analysis. The west Sikhote-Alin Pikeshan Formation volcanics and associated granites occurred at a peak of ~118 Ma and are hosted by the Triassic-Jurassic accretionary complex. Their whole rock geochemistry shows that SiO2 increased in a linear trend, Eu/Eu* values decreased from 0.91 to 0.38, and eNd(t) values decreased from +0.6 to -2.9, indicating magma mixing of a juvenile mantle wedge source and continental crust, consistent with a continental arc. The arc thickened over time with a felsic dike hosted in the Pikeshan granites showing depletion in heavy rare earth elements. The termination of the arc front is documented by the ~107-Ma intermediate lamprophyre and felsic dikes with eNd(t) values of +4.5 to +1.1, indicating an increased mantle contribution over time. Lithospheric extension of the Jiamusi Block to the west occurred at ~100 Ma, characterized by bimodal volcanism and composite dike emplacement, suggestive of asthenosphere upwelling. Based on the spatial and temporal distribution of these igneous rocks, the continental arc and intraplate magmatism migrated eastward contemporaneously. We favor a model invoking rollback of the subducting Paleo-Pacific slab affecting a long-lived continental arc.